2010
DOI: 10.1111/j.1440-1797.2010.01285.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of insulin‐like growth factor binding proteins in normal and proteinuric kidney glomeruli

Abstract: IGFBP-2, -7, -8 and -10 are produced by normal and injured glomerular podocytes and may regulate local IGF-I actions in podocytes and/or cortical tubular cells in the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Interestingly, animal model studies have demonstrated the increased expression of IGFBP-2 in the glomerulus in anti-glomerular basement membrane (GBM) glomerulonephritis in the rat [42] and Murphy Roths Large lymphoproliferation (MRL/ lpr) lupus mice [46]. In human immunoglobulin (Ig)A nephropathy, glomerular expression levels of IGFBP-2 mRNA were increased significantly compared to normal glomeruli [42]. Of relevance to our study, IGFBP-2 has also been reported to be increased in nephrotic syndrome in paediatric patients [19] and as a predictor of longitudinal deterioration of renal function in type 2 diabetes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, animal model studies have demonstrated the increased expression of IGFBP-2 in the glomerulus in anti-glomerular basement membrane (GBM) glomerulonephritis in the rat [42] and Murphy Roths Large lymphoproliferation (MRL/ lpr) lupus mice [46]. In human immunoglobulin (Ig)A nephropathy, glomerular expression levels of IGFBP-2 mRNA were increased significantly compared to normal glomeruli [42]. Of relevance to our study, IGFBP-2 has also been reported to be increased in nephrotic syndrome in paediatric patients [19] and as a predictor of longitudinal deterioration of renal function in type 2 diabetes [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is the second most prevalent serum IGFBP, and has been reported to be a good biomarker of several malignancies . Interestingly, glomerular IGFBP‐2 expression has been reported to be increased in animal models of anti–glomerular basement membrane glomerulonephritis and MRL/lpr lupus . IGFBP‐2 has also been documented to be raised in patients with diabetic nephropathy .…”
Section: Discussionmentioning
confidence: 99%
“…Initial work focused on the mesangial cell [19], showing that this cell produces IGF-I, expresses the IGF-IR and that local IGF-I signalling may be increased in a number of disease states, including diabetes [20]. Recently it has been recognized that the podocyte is also an important source [22] and target [23] of IGF-I, and that IGFs are important for podocyte and glomerular development [24]. Our work has confirmed that IGF-I is produced in the glomerulus and that the podocyte is the major source of this hormone here.…”
Section: Discussionmentioning
confidence: 99%